Assessing Higher-Order Thinking Skills in Physics: A Comparative Study of Paper-Based and Computer-Based Method - Rahman Eka Cahya Rahman Eka Cahya; Budi Jatmiko Budi Jatmiko; Mita Anggaryani; Dwikoranto; Salma Hasna Hamiydah (Universitas Negeri Surabaya, 2025)
Objective: This research is a quasi-experimental investigation with a non-equivalent control group design, aiming to analyse the differences in the use of CBT and PBT methods for HOTs' question assessments. Method: This research employed a quantitative approach, conducting statistical tests using SPSS 26 on each of 35 students by comparing the N-Gain results in the control group using PBT and the experimental group using CBT. Furthermore, normality tests, homogeneity tests, and independent sample-T tests were conducted to determine the significance of the differences between CBT and PBT results. Results: The N-Gain of the experimental group is 0.7652 higher than the N-Gain of the control group is 0.2272. Therefore, the CBT method is more effective than the PBT method. The datum distributed normally and homogeneously both to control group and experimental group, resulting the Sig. (2-tailed) in the independent sample-T test is 0.000 < 0.05. It is concluded, that there is a significant difference between the use of the PBT and CBT methods for assessing HOTs questions. Novelty: This research compares the use of digital and conventional technology in physics learning, especially to improve students' cognitive domain in achieving high-order thinking skills (HOTs), which is one of the important aspects of 21st-century education.